Caracterización de Materias Primas no Metálicas para la Industria Cerámica Plana en los Cantones Catamayo, Chaguarpamba, Olmedo, Paltas y Puyango de la Provincia de Loja, escala 1:50000”. - Angamarca Angamarca, Zaida Celena (2020)
This thesis work called “CHARACTERIZATION OF NON METALLIC RAW MATERIALS FOR THE FLAT CERAMIC INDUSTRY IN THE CANTONCES CATAMAYO, CHAGUARPAMBA, OLMEDO, PALTAS AND PUYANGO OF THE PROVINCE OF LOJA, AT SCALE 1: 50000”, is focused on describing the main properties that raw materials such as clay, feldspar and kaolin must comply with for their industrialization. Once the basic information on the subject under study was compiled, the collection of suitable samples was carried out taking as reference the geology and the map published by INIGEMM in the year 2011 of non-metallic mineralogical indications, to then be subjected to tests both physical, mineralogical and industrial. The samples collected are cataloged each with their respective code according to their place of origin, taking into account the consonants of the canton to which they belong, followed by the letter R indicating that it is a rock, and finally a number assigned in the field under criteria own. After obtaining the results of the tests, each sample was determined and classified within the 3 categories based on the industrial classification of clays (Fernández, García, Lombardero, Sánchez, & Regueiro, 2002), having as follows: for Ball Clays there are 4 samples that meet the requirements CT-R-01, PL-R-10, OL-R-85 and OL-R-104; For loamy clays with low carbonate content there are 5 samples CT-R-02, PL-R-11, PL-R-97, PY-R-73 and CH-R-17; and with regard to the non-plastic non-loamy clays there are 5 samples CT-R-54, PL-R-08, PL-R-21, PY-R-34 and PY-R-72 each with their own characteristics in Regarding clays, and also for feldspars as type of ore I, II, and III, which according to the results it was established that in the study carried out 5 samples were obtained for type of ore I, according to their K2O content . The characterization of the raw material achieved through this study will be subsequently organized, collected and stored in a database created through the QGIS software, which will be extended to the web, through a public access platform, completing this information with INIGEMM mineralogical evidence and studies of several other authors, each sample will be georeferenced and will contain the conclusive results.